Efficacy of sewage sludge derived biochar on enhancing soil health and crop productivity in strongly acidic soil - Junior, Antonio; Guo, Mingxin (Frontiers in Soil Science, 2023)
Converting sewage sludge to biochar to serve as soil amendment and nutrient supplement to cropland may be an environmental benign and value-added approach to recycle the waste. Potting experiments were conducted to examine the efficacy of sludge biochar amendments on enhancing soil health and crop productivity. Strongly acidic soil (pH=5.0) was amended with sludge biochar at three different concentrations: 0 (control), 1% and 2% of its dry weight, and packed into plastic buckets (9.45-L) to a bulk density of 1.1 g cm-3, and each treatment had three replicates. Winter wheat (Triticum aestivum L.), spinach (Spinacia oleracea), and Mung bean (Vigna radiata) were sequentially grown for nine months under greenhouse and field conditions (each crop cycle lasted three months). The above-ground biomass was collected, and oven dried at 65°C for 72 hours to assess plant biomass yield. Soil health parameters such as aggregates stability, pH, electric conductivity (EC), soil respiration, and microbial biomass C were measured. Soils amended with 2% biochar demonstrated higher biomass yield in winter wheat and spinach crops compared to those amended with 1% biochar and unamended control, on the other hand, mung bean did not present significant difference in all treatments. Similarly, 2% biochar demonstrated high aggregates stability (19.85%) followed by control (9%) and 1% biochar (8.3%). Soil acidity was neutralized in soils amended with 2% biochar (pH: 6.5) compared to control (pH: 5.8) and 1% biochar (pH: 5.5). EC was in the ideal level (<2.7 dS m-1) for all treatments. Soil respiration was not significantly different in all treatments. Microbial biomass C was higher in control and 2% biochar with significant differences towards 1% biochar. These findings provide additional evidence that sludge biochar promote plant growth and improve certain soil health parameters. However, the effect of sludge biochar in soil biological properties was not observed. Therefore, long-term field experiments are needed to assess the amendment effect of sludge biochar on microbial biomass C and soil respiration to validate the persistent efficacy of sludge biochar amendments on facilitating crop production, crop productivity, and soil health.